ANALISIS FAKTOR-FAKTOR PENYEBAB KERUSAKAN PRODUK PADA PROSES CETAK PRODUK (Studi Kasus pada Majalah SAKINAH PT. Temprina Media Grafika (Jawa Pos Group) Semarang) - Khodijah, Syarifah Labibah; Rahardjo, Susilo Toto (Diponegoro Journal of Management, 2015)
In 2014 SAKINAH magazine produced by PT. Temprina Media Graphic damage to exceed the standard limit of the company. Standards set by the company was 0.25%. This study aimed to analyze the factors that cause damage to the product in the process of printing products at PT. Temprina Media Graphic Semarang. The data used are primary and secondary data. Samples were examined by 100 respondents. The number of variables examined in this study were 20 variables. The data were then analyzed using factor analysis in SPSS 16.0 for Windows.            The results showed that of the 20 variables had been reduced and no variables excluded from the model because it has met the criteria MSA> 0.5. From the test results obtained by factor analysis of 20 variables that persist in the model and breaks into 6 factors, are all factors that influence the breakdown products in product printing processes. These factors are factors Continuity Engines Work with eigenvalues 6446 values, factors Readiness Control Method / System Working with eigenvalues values 1831, Readiness Materials and Work Order with eigen value 1,621 values, process control factors with eigenvalues 1266 values, factors Work Discipline with eigenvalues values 1169, and Supervisor Support factors with eigenvalues 1,011 values. 6th factor is obtained based on the value of eigen values greater than one. Dominating factor is the factor that has a Sustainability Working Machines values eigenvalues of 6446 with a percentage of 32 230% variance.            Factors such form, then performed the analysis using method Fishbone Diagram to determine the causal factors in the chart, so that the company can take preventive and corrective measures to reduce the level of damage and improve product quality.